BENTUK SAPAAN KEKERABATAN DALAM BAHASA BANJAR DI TEMBILAHAN, RIAU - R. Saleh (Balai Bahasa Provinsi Riau, 2017)
This study aims to describe forms of kinship terms of address used in Banjar language. The method used in this research is the descriptive qualitative method. The data were collected through an interview in which the results of the interview are jot down. The data were analyzed with unified method with the following steps; classifying the data according to their kinds, describing each terms of address, and providing examples of the terms of address (matching) ina sentence. The result of this study reveals kinship terms of address based on the line of descent are abah, uwak laki, uwak bini, nanang, acik, abang, kakak, ading, anak, cucu, nenek laki, and datuk. While kinship terms of address based on the line of mariage are umak, abah mintuhak, umak mintuhak, nenek bini, nenek laki, nanang, acik, ulak, uwak, mantu, bini, laki, kakak ipar, abang ipar, and ading ipar. The study concludes that there are two forms of kinship terms of address used in Banjar language, namely kinship terms of address based on line of descent and line of marriage.